(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to formulate a quality model of e-management in higher education academic services. Through a qualitative approach, researchers conducted studies by means of spreading instruments. The qualitative results were deepened by conducting interviews with respondents at three universities, namely Pamulang University, Garut University, and Muhammadiyah Cirebon University. The research results obtained the following findings: 1) e-management planning has been going well; 2) support for the management system in the aspects of finance, access and network, as well as information documentation still needs to be improved; 3) the sustainability of e-management development has gone well when compared to handling non-conformities and corrective actions; 4) dimensions of internal audit, monitoring, assessment and evaluation analysis, as well as management reviews in the performance evaluation variable are carried out properly; and 5) the dimension of responsibility for the leadership variable still needs to be improved. The conclusion of this research was that planning arrangement is the dimension with the lowest respondent’s perception compared to the other two dimensions, namely the combination of plan and plan design. In the aspect of management system support, it is clear that funding, access and networks, as well as documentation of information are perceived to be insufficient.